All-organic aqueous zinc ion battery positive electrode material as well as preparation method and application thereof
By adopting organic positive electrode materials with adjustable structures and relatively stable organic negative electrodes, combined with water-based electrolyte, the problems of low zinc utilization rate of zinc ion batteries and limited development of inorganic positive electrode materials are solved, and the stable charging and discharge and environmental protection of all organic water-based zinc ion batteries are achieved.
Patent Information
- Application Number
- CN202510008656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The zinc utilization rate of existing zinc ion batteries is low, and the development of inorganic positive electrode materials is restricted by the problems of limited mineral resources and environmental pollution, which leads to the safety and high cost of lithium-ion batteries that limit their large-scale applications.
Organic positive electrode materials with adjustable structure and rich elements are used, such as 5,5,12,12'-tetrahydro-2,2'-biquinoxaline[2,3-b]quinoxaline, combined with relatively stable imine and carbonyl organic negative electrodes, and use environmentally friendly and safe water-based electrolyte to form an all-organic water-based zinc ion battery.
The stable charging and discharge of all organic water-based zinc ion batteries is achieved, which improves the utilization rate of zinc, reduces production costs, and reduces environmental pollution due to the environmental protection and safety of the materials.
Smart Images

Figure CN119798283A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials and batteries, and in particular to an all-organic aqueous zinc ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Although state-of-the-art lithium-ion batteries dominate the portable electronics and electric vehicle markets, their safety and high cost issues limit their large-scale application. In contrast, aqueous zinc-ion batteries (ZIBs) have a very high theoretical capacity (820 mAh g -1 ), good compatibility with aqueous electrolytes, abundant natural resources and low toxicity, have attracted widespread attention.
[0003] Currently, inorganic cathodes such as manganese oxides, vanadium oxides, and Prussian blue analogs are commonly used in ZIBs. However, the development of these materials has been severely hampered by limited mineral resources and serious environmental pollution problems. In recent years, organic electrode materials have become attractive cathode candidates due to their inherent advantages of structural diversity and sustainability. Existing organic cathode materials have a low operating voltage, which significantly limits their application potential. Therefore, designing a high-voltage organic cathode material has become a research hotspot.
[0004] A key issue that is often overlooked in zinc-organic batteries is the low zinc utilization rate. Dendrite growth and side reactions of zinc in aqueous electrolytes result in poor coulombic efficiency of zinc anodes, which is difficult to meet practical applications. The use of organic anodes can improve these problems.
[0005] As a new type of secondary battery, all-organic aqueous batteries combine the advantages of rich variety and easily adjustable structure of organic compounds with the safety, environmental protection and low cost of aqueous electrolytes, and have great potential in the field of energy storage applications. Summary of the invention
[0006] The purpose of the present invention is to provide a positive electrode material for an all-organic aqueous zinc ion battery, a preparation method and application thereof, which adopts an organic positive electrode with adjustable structure and rich elements, a relatively stable imine and carbonyl organic negative electrode, and an environmentally friendly and safe water-based electrolyte to achieve stable charging and discharging of the all-organic aqueous zinc ion battery.
[0007] To achieve the above object, the present invention provides an all-organic aqueous zinc ion battery positive electrode material, the positive electrode material is 5,5,12,12'-tetrahydro-2,2'-biquinoxalino[2,3-b]quinoxaline, and its structural formula is shown in Formula 1:
[0008] Formula 1:
[0009] The present invention provides a method for preparing an all-organic aqueous zinc ion battery positive electrode material, comprising the following steps:
[0010] S1, adding a first reactant and a second reactant into a container for pretreatment;
[0011] S2, treating the product obtained in S1 again, and cooling to room temperature after the reaction is completed;
[0012] S3. The product obtained in S2 is treated, washed, and vacuum-dried to obtain a positive electrode material.
[0013] Preferably, the specific operations are as follows:
[0014] S1. Add the first reactant and the second reactant into a three-necked flask, and add N,N-dimethylformamide to obtain a mixed solution;
[0015] S2, heating the mixed solution to reflux, and cooling to room temperature after the reaction is completed to obtain product 1;
[0016] S3. The product 1 is vacuum filtered, washed alternately with N,N-dimethylformamide and water, and vacuum dried to obtain a positive electrode material.
[0017] Preferably, in S1, the amount of the first reactant and N,N-dimethylformamide used is 7-8 mL of N,N-dimethylformamide per mmol of the first reactant.
[0018] Preferably, the specific operations are as follows:
[0019] S1, weighing a first reactant and a second reactant, mixing and grinding to obtain a mixture;
[0020] S2, heating the mixture to react, and cooling to room temperature after the reaction is completed to obtain product 2;
[0021] S3. Disperse the product in water, wash and vacuum dry to obtain the positive electrode material.
[0022] Preferably, the first reactant is a compound of the dichloro quinoxaline type, which is one or more of 2,3-dichloroquinoxaline, 6-bromo-2,3-dichloroquinoxaline, 2,3-dichloro-6-methylquinoxaline, 2,3-dichloro-6,7-difluoroquinoxaline, 2,3-dichloro-6-methoxyquinoxaline, 2,3-dichloro-6,7-dinitroquinoxaline, 2,3-dichloro-6,7-dimethylquinoxaline, and 2,3-dichloro-6,7-dimethoxyquinoxaline;
[0023] The second reactant is a compound having an o-aniline structure, which is one or more of 3,3-diaminobenzyl diamine, 4,5-difluoro-1,2-phenylenediamine, 4-methoxy o-phenylenediamine, 4-nitro o-phenylenediamine, 4-bromo-1,2-phenylenediamine, and 4-fluoro-1,2-phenylenediamine.
[0024] Preferably, in S1, the molar ratio of the first reactant to the second reactant is 1:(1-1.2);
[0025] In S2, the heating temperature is 120-180°C and the heating time is 5-10h;
[0026] In S3, the washing times are 3-5 times, the drying temperature is 80-100°C, and the drying time is 10-12h.
[0027] The invention provides an application of an all-organic aqueous zinc ion battery positive electrode material. The all-organic aqueous zinc ion battery positive electrode material is applied to an all-organic aqueous zinc ion battery. The all-organic aqueous zinc ion battery comprises an organic positive electrode, an organic negative electrode and a water-based electrolyte.
[0028] Preferably, the method comprises the following steps:
[0029] A. Add the positive electrode material and the negative electrode material and Ketjen black into a mortar and grind them respectively, then drop an N-methylpyrrolidone solution containing 2% polytetrafluoroethylene binder, wherein the mass ratio of the positive electrode material or the negative electrode material to Ketjen black and polytetrafluoroethylene is (6-7):3:1, mix them evenly and apply them on a stainless steel mesh current collector, put them in a vacuum drying oven and dry them at 70-90° C. for 10-14 hours, and then cut them into discs with a diameter of 10 mm to obtain an organic positive electrode or an organic negative electrode;
[0030] B. Separate the organic positive electrode and the organic negative electrode with a glass fiber separator and inject a water-based electrolyte;
[0031] The water-based electrolyte is an electrolyte formed by dissolving one or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, zinc chloride, and zinc perchlorate in water.
[0032] Preferably, in A, the negative electrode material is an imine organic substance, which is one of dipyridophenazine and dipyridoquinoxaline, and its structural formula is shown in Formula 2 and Formula 3:
[0033] Formula 2: Bipyridophenazine;
[0034] Formula 3: Bipyridoquinoxaline;
[0035] Alternatively, the negative electrode material is a carbonyl organic compound, which is one of 1,4,5,8-naphthalenetetracarboxylic anhydride or 3,4,9,10-tetracarboxylic anhydride, and its structural formula is shown in Formula 4 and Formula 5:
[0036] Formula 4: 1,4,5,8-Naphthalenetetracarboxylic anhydride;
[0037] Formula 5: 3,4,9,10-Tetracarboxylic anhydride.
[0038] Therefore, the present invention adopts the above-mentioned all-organic aqueous zinc ion battery positive electrode material and its preparation method and application, which has the following beneficial effects:
[0039] (1) Using nitrogen heterocyclic organic compounds as positive electrode materials, the structure is adjustable and the elements are rich, and it has a higher working voltage;
[0040] (2) Using imine and carbonyl organic compounds as negative electrode materials is relatively stable and can achieve stable charging and discharging of all-organic aqueous zinc-ion batteries;
[0041] (3) The water-based electrolyte used is environmentally friendly and safe.
[0042] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an FT-IR spectrum of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and a positive electrode material of application example 1 of the present invention;
[0044] Figure 2 It is a CV diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery of application example 1 of the present invention;
[0045] Figure 3 This is a rate performance diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery according to Example 1 of the present invention;
[0046] Figure 4 This is a cycle performance diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery according to Example 1 of the present invention;
[0047] Figure 5 It is a charge and discharge curve diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery of application embodiment 2 of the present invention;
[0048] Figure 6This is a cycle performance diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery according to the third application example of the present invention;
[0049] Figure 7 It is a charge and discharge curve diagram of an all-organic aqueous zinc ion battery positive electrode material and a preparation method thereof and an all-organic aqueous zinc ion battery of application embodiment 4 of the present invention. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0051] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0052] Embodiment 1
[0053] An all-organic aqueous zinc ion battery positive electrode material, the positive electrode material is 5,5,12,12'-tetrahydro-2,2'-biquinoxalino[2,3-b]quinoxaline, and its structural formula is shown in Formula 1:
[0054] Formula 1:
[0055] A method for preparing an all-organic aqueous zinc ion battery positive electrode material comprises the following steps:
[0056] S1. Add 0.4 g of 2,3-dichloroquinoxaline and 0.25 g of 3,3-diaminobenzidine into a three-necked flask, and add 7 mL of N,N-dimethylformamide to obtain a mixed solution.
[0057] S2, heating the mixed solution under reflux at 120° C. for 5 h, cooling to room temperature after the reaction is completed, to obtain product 1;
[0058] S3. The product 1 was vacuum filtered, washed alternately with N,N-dimethylformamide and water for 3 times, placed in a vacuum drying oven, and dried at 80° C. for 12 h to obtain a positive electrode material.
[0059] The prepared positive electrode material is applied to an all-organic aqueous zinc ion battery, wherein the all-organic aqueous zinc ion battery comprises an organic positive electrode, an organic negative electrode and a water-based electrolyte, and specifically comprises the following steps:
[0060] A. Add 0.06g of 5,5,12,12'-tetrahydro-2,2'-biquinoxalino[2,3-b]quinoxaline and 0.03g of Ketjen black conductive agent into a mortar and grind them thoroughly. Then, drop 0.5g of NMP (N-methylpyrrolidone) solution containing 2% polytetrafluoroethylene binder, mix well, apply it on the stainless steel mesh current collector, put it in a vacuum drying oven at 80°C for 12h, and then cut it into 10mm diameter discs to obtain an organic positive electrode;
[0061] B. Add 0.06g of dipyridophenazine and 0.03g of Ketjen black conductive agent into a mortar and grind them thoroughly. Then add 0.5g of NMP (N-methylpyrrolidone) solution containing 2% polytetrafluoroethylene binder, mix well and apply it on the stainless steel mesh current collector, put it in a vacuum drying oven at 80°C for 12h, and then cut it into 10mm diameter discs to obtain an organic negative electrode;
[0062] C. Use a glass fiber separator to separate the organic positive electrode and the organic negative electrode, and inject 1 mol / L Zn(OTF)2 electrolyte.
[0063] Embodiment 2
[0064] Different from the first embodiment, in C, the water-based electrolyte is a 1 mol / L ZnSO4 electrolyte.
[0065] Embodiment 3
[0066] Different from the first embodiment, in C, the water-based electrolyte is a 1 mol / L Zn(AC)2 electrolyte.
[0067] Embodiment 4
[0068] The difference from Example 1 is that in Example B, the negative electrode material is 0.06 g of dipyridoquinoxaline.
[0069] Experimental Test 1
[0070] Figure 1 This is the FT-IR spectrum of the positive electrode material prepared in Example 1. -1 and 533cm -1 The peaks at correspond to the stretching and bending vibrations of -NH-, respectively, which indicates that the compound was successfully synthesized.
[0071] Experimental Test 2
[0072] Figure 2 This is a CV curve diagram of the all-organic aqueous zinc ion battery prepared in Example 1 at a scan rate of 0.2 mV / s. The results show that both the organic positive electrode and the organic negative electrode exhibit good redox reversibility, and the redox potentials are within the electrochemical window of the electrolyte, so the all-organic aqueous zinc ion battery can work normally.
[0073] Experimental Test Three
[0074] Figure 3 This is a rate performance diagram of the all-organic aqueous zinc ion battery prepared in Example 1. It can be seen from the figure that the battery can return to the initial state after a small current and multiple current cycles. The results show that it has good rate performance.
[0075] Experiment Test 4
[0076] Figure 4 This is a cycle performance diagram of the all-organic aqueous zinc ion battery prepared in Example 1, indicating that the battery has good cycle stability.
[0077] Experiment Test Five
[0078] Figure 5 This is a partial charge and discharge curve diagram of the all-organic aqueous zinc ion battery prepared in Example 2. It can be observed that the coulombic efficiency gradually increases, indicating that the all-organic aqueous zinc ion battery requires an activation process to improve its charge and discharge efficiency.
[0079] Experimental Test 6
[0080] Figure 6 This is a cycle performance diagram of the all-organic aqueous zinc ion battery prepared in Example 3, indicating that the all-organic aqueous zinc ion battery has good cycle performance.
[0081] Experimental Test 7
[0082] Figure 7 The first five cycles of charge and discharge curves of the all-organic aqueous zinc ion battery prepared in Example 4 show that the median voltage is about 0.40 V, and the battery has a relatively stable cycle performance. Based on the active mass of the positive electrode material, the battery -1 At a current density of , the first cycle charge capacity is 247.385 mAh g -1 , the discharge capacity is 123.997 mAh g -1 .
[0083] Therefore, the present invention adopts the above-mentioned all-organic aqueous zinc ion battery positive electrode material and its preparation method and application, adopts a structurally adjustable and element-rich organic positive electrode, a relatively stable imine and carbonyl organic negative electrode, and an environmentally friendly and safe water-based electrolyte, so as to achieve stable charging and discharging of the all-organic aqueous zinc ion battery.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An all-organic aqueous zinc ion battery positive electrode material, characterized in that: The positive electrode material is 5,5,12,12'-tetrahydro-2,2'-biquinoxalino[2,3-b]quinoxaline, and its structural formula is shown in Formula 1: Formula 1:
2. A method for preparing the all-organic aqueous zinc ion battery positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: S1, adding a first reactant and a second reactant into a container for pretreatment; S2, treating the product obtained in S1 again, and cooling to room temperature after the reaction is completed; S3. The product obtained in S2 is treated, washed, and vacuum-dried to obtain a positive electrode material.
3. The method according to claim 2, characterized in that The specific operations are as follows: S1. Add the first reactant and the second reactant into a three-necked flask, and add N,N-dimethylformamide to obtain a mixed solution; S2, heating the mixed solution to reflux, and cooling to room temperature after the reaction is completed to obtain product 1; S3. The product 1 is vacuum filtered, washed alternately with N,N-dimethylformamide and water, and vacuum dried to obtain a positive electrode material.
4. The method according to claim 3, characterized in that In S1, the amounts of the first reactant and N,N-dimethylformamide are such that 7-8 mL of N,N-dimethylformamide is used to dissolve each mmol of the first reactant.
5. The method according to claim 2, characterized in that: The specific operations are as follows: S1, weighing a first reactant and a second reactant, mixing and grinding to obtain a mixture; S2, heating the mixture to react, and cooling to room temperature after the reaction is completed to obtain product 2; S3. Disperse the product in water, wash and vacuum dry to obtain the positive electrode material.
6. The method according to claim 3 or 5, characterized in that: The first reactant is a compound of the dichloro quinoxaline type, which is one or more of 2,3-dichloroquinoxaline, 6-bromo-2,3-dichloroquinoxaline, 2,3-dichloro-6-methylquinoxaline, 2,3-dichloro-6,7-difluoroquinoxaline, 2,3-dichloro-6-methoxyquinoxaline, 2,3-dichloro-6,7-dinitroquinoxaline, 2,3-dichloro-6,7-dimethylquinoxaline, and 2,3-dichloro-6,7-dimethoxyquinoxaline; The second reactant is a compound having an o-aniline structure, which is one or more of 3,3-diaminobenzyl diamine, 4,5-difluoro-1,2-phenylenediamine, 4-methoxy o-phenylenediamine, 4-nitro o-phenylenediamine, 4-bromo-1,2-phenylenediamine, and 4-fluoro-1,2-phenylenediamine.
7. The method according to claim 3 or 5, characterized in that: In S1, the molar ratio of the first reactant to the second reactant is 1:(1-1.2); In S2, the heating temperature is 120-180°C and the heating time is 5-10h; In S3, the washing times are 3-5 times, the drying temperature is 80-100°C, and the drying time is 10-12h.
8. An application of an all-organic aqueous zinc ion battery positive electrode material, characterized in that: The all-organic aqueous zinc ion battery positive electrode material described in claim 1 is applied to an all-organic aqueous zinc ion battery, and the all-organic aqueous zinc ion battery comprises an organic positive electrode, an organic negative electrode and a water-based electrolyte.
9. The use of an all-organic aqueous zinc ion battery positive electrode material according to claim 8, characterized in that: The following steps are involved: A. Add the positive electrode material and the negative electrode material and Ketjen black into a mortar and grind them respectively, then drop an N-methylpyrrolidone solution containing 2% polytetrafluoroethylene, wherein the mass ratio of the positive electrode material or the negative electrode material to Ketjen black and the polytetrafluoroethylene is (6-7):3:1, mix them evenly and apply them on a stainless steel mesh current collector, put them in a vacuum drying oven and dry them at 70-90° C. for 10-14 hours, and then cut them into discs with a diameter of 10 mm to obtain an organic positive electrode or an organic negative electrode; B. Separate the organic positive electrode and the organic negative electrode with a glass fiber separator and inject a water-based electrolyte; The water-based electrolyte is an electrolyte formed by dissolving one or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, zinc chloride, and zinc perchlorate in water.
10. The use according to claim 9, characterized in that: In A, the negative electrode material is an imine organic substance, which is one of dipyridophenazine and dipyridoquinoxaline, and its structural formula is shown in Formula 2 and Formula 3: Formula 2: Bipyridophenazine; Formula 3: Bipyridoquinoxaline; Alternatively, the negative electrode material is a carbonyl organic compound, which is one of 1,4,5,8-naphthalenetetracarboxylic anhydride or 3,4,9,10-tetracarboxylic anhydride, and its structural formula is shown in Formula 4 and Formula 5: Formula 4: 1,4,5,8-Naphthalenetetracarboxylic anhydride; Formula 5: 3,4,9,10-Tetracarboxylic anhydride.
Citation Information
Patent Citations
Organic positive electrode of aqueous zinc ion battery and battery
CN117219767A
N-type organic positive electrode material and preparation method and application thereof
CN118702694A
Quinoxaline polymers
US3563917A
Cited By
Pyridyl phenazine aqueous positive electrode material and preparation method and application thereof
CN121318972A